ANALISIS ATRIBUT-ATRIBUT PRODUK HONDA BRIO SATYA DAN PENGARUHNYA TERHADAP KEPUASAN KONSUMEN - Agus Salim (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2017)
On this globalization era, the number of needs in transportation is increasing, especially in urban society whereupon the number of its mobility is higher than others. Transportation is important part in every single country whether public transportation or not. Recently, Indonesia’s government launched LCGC (Low Cost Green Car) product in many brands. Therefore, Author is only interested in doing research on Honda Brio Satya’s Product Attribute on Customer Satisfaction. The supporting theories which were used in this research are the definition of marketing, product including the elements, product attribute with their dimensions consist of product quality, product feature, and product design, and also customer satisfaction. The object of this study was product attribute and customer satisfaction of Honda Brio Satya.This study used descriptive method using questionnaires for collecting data. For sampling, non-probability sampling with judgment sampling technique were used. Therefore, the questionnaires were distributed through Honda Brio Satya’s Community with 100 respondents. The procedure which was used in the development and testing of model and also data processing was Simple Linear Regression by using SPSS 19. The result of research represented respondents were agree that product attribute variable is the point to consider on customer satisfaction. Besides, respondents were very agree that they are very satisfied on Honda Brio Satya. Therefore, product attribute variable has significant effect to the customer satisfaction. In conclusion, product attribute variable affects customer satisfaction. therefore, if the product attribute is better, the number of customer satisfaction is higher. Keyword : Product attribute, Consumer satisfaction, Product attribute, Product feature, Product design